2017
DOI: 10.1159/000484129
|View full text |Cite
|
Sign up to set email alerts
|

Superior Mesenteric Artery Syndrome Improved by Enteral Nutritional Therapy according to the Controlling Nutritional Status Score

Abstract: Superior mesenteric artery syndrome (SMAS) is a relatively rare disease that involves bowel obstruction symptoms, such as vomiting and gastric distension, owing to the compression of the third portion of the duodenum from the front by the superior mesenteric artery (SMA) and from the rear by the abdominal aorta and the spine. SMAS is diagnosed on the basis of an upper gastrointestinal examination series indicating the obstruction of the third portion of the duodenum or a computed tomography scan indicating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…As the cause of SMAS might be related to loss of intraabdominal adipose tissue, the nutritional status of patients with SMAS requires attention. A previous report has described a 78-year-old woman diagnosed with SMAS after a laparoscopic right hemicolectomy for cecal cancer, whose condition was improved by EN therapy, delivered with a feeding tube, passed through the narrow segment, and placed into the jejunum [5]. The authors used the Controlling Nutritional Status score to assess the patient's nutritional status.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the cause of SMAS might be related to loss of intraabdominal adipose tissue, the nutritional status of patients with SMAS requires attention. A previous report has described a 78-year-old woman diagnosed with SMAS after a laparoscopic right hemicolectomy for cecal cancer, whose condition was improved by EN therapy, delivered with a feeding tube, passed through the narrow segment, and placed into the jejunum [5]. The authors used the Controlling Nutritional Status score to assess the patient's nutritional status.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Given its lack of specific symptoms, SMAS diagnosis remains challenging. Currently, SMAS is diagnosed based on a computed tomography scan or an upper gastrointestinal examination series, showing the narrowing of the branch angle between the aorta and the SMA or the obstruction of the third portion of the duodenum [5]. It has been reported that the aorta -SMA angle in patients with SMAS is 6-22°, compared to 25-60° in healthy persons [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Besides nutritional supporting [17] and decubitus position, the rehabilitating practice after discharge is also important to reduce recurrence. We recommend the rehabilitating practice after discharge, such as appropriate swimming, which is beneficial to enhance the abdominal wall and reduce the frequency of recurrence, especially for female patient.…”
Section: Discussionmentioning
confidence: 99%
“…Management of SMA syndrome varies from medical to surgical procedures aiming to promote weight gain and to increase retroperitoneal fat tissue. Medical management via enteral nutrition given through a feeding tube bypassing the obstruction or a parenteral nutrition with or without prokinetic agents are the preferred strategies and has been proven to be successful in certain cases [20,21]. Knee-chest or side-lying positional change after a meal had been tried to provide partial obstruction relief by widening the aortomesenteric angle [22,23].…”
Section: Discussionmentioning
confidence: 99%